Agenesis of left lung in an adult female: A rare case report - Rupam Kumar Ta; Sourindra Nath Banerjee; Kaliprasanna Chatterjee (Wolters Kluwer Medknow Publications, 2015)
Pulmonary agenesis is a rare congenital anomaly presenting usually with recurrent chest infection in early childhood with an annual incidence of 1 out of 100,000 births. Nearly half of the cases were usually associated with congenital co-anomaly of other organ(s). Diagnosis in adulthood is very rare. We reported here an extremely rare case of left lung agenesis in a 19 year girl presenting with dry cough and breathlessness for one month with an abnormal chest x-ray. Diagnosis was made with the aid of contrast enhanced Computed Tomotram [CECT] thorax and fibre-optic bronchoscope. Prognosis depends on affected side, existing lung tissue and other anomalies (if present). However, we managed the case conservatively. We want to add this rare case into the pool of lung agenesis cases report.